Differential effects of small extracellular vesicles from head and neck cancer patients on dendritic cell functions - Huber, Diana; Yerneni, Sai Gopal Krishna; Hofmann, Linda; Ludwig, Sonja; Hoffmann, Thomas K.; Wollenberg, Barbara; Whiteside, Theresa L.; Theodoraki, Marie-Nicole (Frontiers in oncology, 2026)
BackgroundTumor-derived small extracellular vesicles were shown to contribute to immunosuppression in various cancer types, including head and neck squamous cell carcinoma. Dendritic cells, major regulators of specific anti-tumor immune response, are often impaired in their function in the context of cancer.MethodsMonocyte-derived dendritic cells were incubated with isolated small extracellular vesicles during or after maturation. Cell surface markers and antigen processing machinery were assessed by flow cytometry. Vesicle-treated dendritic cells were tested for interleukin 12p70 production by ELISA, and differences in uptake of labeled vesicles were shown by confocal microscopy.ResultsSmall extracellular vesicles derived from HPV(+) tumor cell lines increased maturation and activation of immature dendritic cells, priming them for more rapid phagocytosis. Immature dendritic cells co-incubated with vesicles had lower levels of antigen presenting machinery components and produced less IL12p70 than controls, while similarly co-incubated mature dendritic cells remained unaffected. Vesicles in plasma of patients with head and neck cancer inhibited functions of mature dendritic cells by downregulating expression of antigen presenting machinery components.ConclusionOur results uncover mechanisms through which tumor-derived small extracellular vesicles modulate dendritic cell functions locally and systemically. These mechanisms may also affect dendritic cell-based vaccine efficacy.
Gesehen am 16.02.2026